An exploration of Service Design Jam and its ability to foster Social Enterprise - Kuzmina, Ksenija; Parker, Chris; Jun, Gyuchan Thomas; Maguire, Martin; Mitchell, Val; Moreno, Mariale; Porter, Samantha (Design Research Society, 2016)
Social enterprises (SE) are valued as innovative solutions to complex problems but require conditions to nurture and support them. Most support systems rely on individuals who already have an SE idea, and there is very little research on understanding what conditions can support to cultivate the willingness and motivation to engage individuals in this activity. An exploratory study was led to understand whether a particular event, Service Design Jams can provide such conditions. The paper introduces the study of the Lufbra Jam, organised at Loughborough University, from which two social enterprises, Crop Club in 2013, and FrenPal in 2014 emerged. Through literature review desirability and feasibility were extrapolated as key variables to the formation process of social enterprises. A focus group with three Lufbra Jam organisers was led to identify important organisational elements of the Jam that were perceived to have an impact on the formation of the successful SE thus influencing the perception of desirability and feasibility of SE in individuals. The integration of the two created a thematic matrix that was used to analyse findings from the research with the participants of the two successful SE Cases. The research findings suggest that Lufbra Jam enabled individuals to identify socially and environmentally focused issues and formulate service solutions that they deemed to be desirable and feasible ideas. It also provided an insight that winning and an enterprising workshop were important SDJ elements that helped teams to recognise their service ideas not only as feasible solutions but as SE opportunity for the team to take forward.
Keywords: service design; social enterprise; social innovation; social value